Enzymatic acylation of di- and trisaccharides with fatty acids: choosing the appropriate enzyme, support and solvent - Plou Gasca, Francisco José; Cruces Villalobos, María Ángeles; Ferrer, Manuel; Fuentes Ledo, Gloria; Pastor Martínez, Eitel; Bernabé, Manuel; Christensen, Morten; Comelles, Francesc; Parra Juez, José Luis; Ballesteros Olmo, Antonio (Journal of Biotechnology, 2009)
Enzymatic synthesis of fatty acid esters of di- and trisaccharides is limited by the fact that most biological catalysts are inactivated by the polar solvents (e.g. dimethylsulfoxide, dimethylformamide) where these carbohydrates are soluble. This article reviews the methodologies developed to overcome this limitation, namely those involving control over the reaction medium, the enzyme and the support. We have proposed the use of mixtures of miscible solvents (e.g. dimethylsulfoxide and 2-methyl-2-butanol) as a general strategy to acylate enzymatically hydrophilic substrates. We observed that decreasing the hydrophobicity of the medium (i.e. lowering the percentage of DMSO) the molar ratio sucrose diesters vs. sucrose monoesters can be substantially enhanced. The different regioselectivity exhibited by several lipases and proteases makes feasible to synthesize different positional isomers, whose properties may vary considerably. In particular, the lipase from Thermomyces lanuginosus displays a notable selectivity for only one hydroxyl group in the acylation of sucrose, maltose, leucrose and maltotriose, compared with lipase from Candida antarctica. We have examined three immobilisation methods (adsorption on polypropylene, covalent coupling to Eupergit C, and silica-granulation) for sucrose acylation catalyzed by T. lanuginosus lipase. The morphology of the support affected significantly the reaction rate and/or the selectivity of the process We are grateful to Loreto Bajón (Instituto de Catálisis) for technical help with electron microscopy. We are indebted to Jordi Sucrana (Degusa Texturant Systems, Barcelona, Spain) and Naoya Otomo (Mitsubishi Kagaku Foods Co., Tokyo, Japan) for technical help. We thank Comunidad de Madrid and Ministerio de Ciencia y Tecnología for research fellowships. This work was supported by the E.U. (Project BIO4-CT98-0363), the Spanish CICYT (Projects BIO98-0793 and BIO1999-1710-CE), and Comunidad de Madrid (Project 07G/0042/2000) Peer reviewed